2010
DOI: 10.1111/j.1365-2958.2010.07363.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of nitrate assimilation in Aspergillus nidulans reveals connections to nitric oxide metabolism

Abstract: Nitrate is a dominant form of inorganic nitrogen (N) in soils and can be efficiently assimilated by bacteria, fungi and plants. We studied here the transcriptome of the short-term nitrate response using assimilating and non-assimilating strains of the model ascomycete Aspergillus nidulans. Among the 72 genes positively responding to nitrate, only 18 genes carry binding sites for the pathway-specific activator NirA. Forty-five genes were repressed by nitrate metabolism. Because nirA- strains are N-starved at ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
88
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 97 publications
5
88
0
1
Order By: Relevance
“…Its role in detoxifying harmful RNIs during hypoxia remains unclear. Its slight upregulation under these conditions may also simply be explained by a coregulation with FhpA as reported from A. nidulans (40).…”
Section: Gene Expression In Long-term Hypoxia-adapted a Fumigatussupporting
confidence: 54%
See 1 more Smart Citation
“…Its role in detoxifying harmful RNIs during hypoxia remains unclear. Its slight upregulation under these conditions may also simply be explained by a coregulation with FhpA as reported from A. nidulans (40).…”
Section: Gene Expression In Long-term Hypoxia-adapted a Fumigatussupporting
confidence: 54%
“…To elucidate the role of the flavohemoprotein FhpA during hypoxia, we characterized its regulation in more detail. In aspergilli, the NO dioxygenase activity of flavohemoproteins suggests a role in the detoxification of nitric oxide (NO), which is formed during nitrate assimilation (39,40). In agreement, it was shown that fhpA is expressed in the presence of nitrate but repressed when glutamine is used as sole nitrogen source (K. Lapp, M. Vödisch, K. Kroll, M. Strassburger, O. Kniemeyer, T. Heinekamp, and A.…”
Section: Gene Expression In Long-term Hypoxia-adapted a Fumigatusmentioning
confidence: 84%
“…FAD is a crucial coenzyme of flavohemoglobins, which provide protection against NO and related reactive nitrogen species [24]. We therefore tested the growth of Δ riboB during NO stress, induced by addition of 5 mM NaNO 2 at a low pH of 4.0 (acidic conditions stimulate generation of nitric oxide from nitrate [25]), and limiting 2.5 µM riboflavin for growth. Growth of the mutant was inhibited compared to the wt and complemented strains, indicating an important role for riboflavin in nitric oxide (NO) detoxification (Figure 3(a)).…”
Section: Resultsmentioning
confidence: 99%
“…Aspergillus nidulans harbors two predicted paralogs that encode cytosolic FHbA and mitochondrial FHbB (32). We constructed an A. nidulans strain in which both paralogs were deleted (⌬fhb) (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports indicate that A. oryzae produces two FHb isozymes that function as NODs and that they are located in the cytosol and mitochondria (40,41). Aspergillus nidulans is a powerful model organism of the genus Aspergillus that produces FHb in order to survive under nitrosative stress (32). We previously reported that A. nidulans dissimilated nitrate to generate ammonium via NO 2 Ϫ under hypoxic conditions (36).…”
mentioning
confidence: 99%